A diplomacy woven with textiles: Medici-Ottoman relations during the late Renaissance. Issue 2 (2nd July 2020) - Özden Mercan, F.
Abstract : This article focuses on the relations of the Medici dukes with the Ottoman Empire in the second half of the sixteenth century, exploring the complex backdrop to the diplomatic negotiations that took place over the 1570s and 1590s. Due to periods of stagnation and crisis in the Florentine woollen industry, textile manufacturers and cloth merchants urged the Grand Duchy to resume diplomatic contacts with the Sublime Porte so that they could penetrate the Ottoman market and increase the volume of their exports. A significant challenge faced by Florence was rivalry from other states conducting trade in the Ottoman lands, especially the Venetians. Seeing the attempts of the Florentines to infiltrate the Ottoman market by producing counterfeit Venetian woollens, Venice became a strong opponent of Florentine diplomacy at the Porte. Tracing the experiences of the Florentine textile industry, specifically the woollen cloth industry, this article argues that the Arte della Lana played an important role in shaping the Medici diplomacy with the Sublime Porte in the second half of the sixteenth century. Moreover, the rivalry between Venice and Florence over dominating the Ottoman textile market stimulated transfer of technical knowledge, new production techniques and new types of cloth in order to gain a place in this market.